Characterization and genome analysis of phage vB_KpnS_SXFY507 against Klebsiella pneumoniae and efficacy assessment in Galleria mellonella larvae - Feng, Jiao; Li, Fei; Sun, Li; Dong, Lina; Gao, Liting; Wang, Han; Yan, Liyong; Wu, Changxin (Frontiers in Microbiology, 2023)
Carbapenem-resistant Klebsiella pneumoniae is one of the primary bacterial pathogens that pose a significant threat to global public health because of the lack of available therapeutic options. Phage therapy shows promise as a potential alternative to current antimicrobial chemotherapies. In this study, we isolated a new Siphoviridae phage vB_KpnS_SXFY507 against KPC-producing K. pneumoniae from hospital sewage. It had a short latent period of 20 min and a large burst size of 246 phages/cell. The host range of phage vB_KpnS_SXFY507 was relatively broad. It has a wide range of pH tolerance and high thermal stability. The genome of phage vB_KpnS_SXFY507 was 53,122 bp in length with a G+C content of 49.1%. A total of 81 ORFs and no virulence or antibiotic resistance related genes were involved in the phage vB_KpnS_SXFY507 genome. Phage vB_KpnS_SXFY507 showed significant antibacterial activity in vitro. The survival rate of Galleria mellonella larvae inoculated with K. pneumoniae SXFY507 was 20%. The survival rate of K. pneumonia-infected G. mellonella larvae was increased from 20% to 60% within 72 h upon treatment with phage vB_KpnS_SXFY507. In conclusion, these findings indicate that phage vB_KpnS_SXFY507 has the potential to be used as an antimicrobial agent for the control of K. pneumoniae.